EXPERIENTIAL LEARNING IN HIGHER EDUCATION: A BIBLIOMETRIC ANALYSIS FROM 1991 TO 2024 - Duc Long, Pham; Thuy Nga, Nguyen; Thi Kim Phuong, Bui (HNUE Journal of Science: Journal of Educational Science, 2026)
Aiming to prepare students to adapt to the rapid changes of a new era, experiential learning activities have been studied extensively. However, previous academic work has primarily focused on specific topics rather than the broader picture. There remains a paucity of studies that systematically synthesise and critically map the development of experiential learning literature. The paper addresses a research gap by conducting a bibliometric analysis of 584 Scopus-indexed articles (1991-2024), using descriptive and science mapping techniques to benefit researchers, lecturers and policymakers by examining the development, trends, and future directions of experiential learning research. The analysis revealed three phases of experiential learning studies in the literature: the budding phase, the fluctuation phase, and the rapid development phase. Among the 20 most-published journals, Q1- and Q2-ranked journals, including the International Journal of Sustainability in Higher Education and the Journal of Experiential Education, primarily contribute to the development of academic knowledge on experiential learning. Furthermore, three thematic clusters, covering technology-based experiential learning, student-centred teaching and learning, and initiatives in engineering education, were identified through keyword analysis regarding the experiential learning research structure. Future research on experiential learning is recommended to focus on educational innovations and sustainable development in the execution of experiential learning activities.